Purse-string contraction guides mechanical gradient-dictated heterogeneous migration of epithelial monolayer. (15th March 2023) - Zhang, Haihui; Xu, Hongwei; Sun, Weihao; Fang, Xu; Qin, Peiwu; Huang, Jianyong; Fang, Jing; Lin, Feng; Xiong, Chunyang
Abstract: Mechanical heterogeneity has been recognized as an important role in mediating collective cell migration, yet the related mechanism has not been elucidated. Herein, we fabricate heterogeneous stiffness gradients by leveraging microelastically-patterned hydrogels with varying periodic distance. We observe that a decrease in the periodic distance of the mechanical heterogeneity is accompanied by an overall increase in the velocity and directionality of the migrating monolayer. Moreover, inhibition of ROCK- and myosin ⅡA- but not Rac1-mediated contraction reduces monolayer migration on the mechanically heterogeneous substrates. Furthermore, we find that F-actin and myosin ⅡA form purse-string at the leading edge on the mechanically heterogeneous substrates. Together, these findings not only show that the orientational cell–cell contraction promotes collective cell migration under the mechanical heterogeneity, but also demonstrate that the mechanosensation arising from large-scale cell–cell interactions through purse-string formation mediated cell–cell orientational contraction can feed back to regulate the reorganization of epithelial tissues. Statement of significance: By detecting the links between heterogenous rigidity and collective cell migration behavior at the molecular level, we reveal that collective cell migration in the mechanical heterogeneity is driven by ROCK- and myosin-ⅡA-dependent cytoskeletal tension. We confirm that cytoskeletal tension across the epithelial tissue is holistically linked through F-actin and myosin-ⅡA, which cooperate to form purse-string structures for modulating collective tissue behavior on the exogenous matrix with mechanical heterogeneity. Mechanical heterogeneity initiates tissue growth, remodelling, and morphogenesis by orientating cell contractility. Therefore, tensional homeostasis across large-scale cell interactions appears to be necessary and sufficient to trigger collective tissue behavior. Overall, these findings shed light on the role of mechanical heterogeneity in tissue microenvironment for reorganization and morphogenesis. Graphical abstract: Image, graphical abstract